Interstitial Tubal Ectopic Pregnancy: A Very Rare Variety (Bangladesh Medical Journal, 2010)
A 28 years old lady, para 2+0 presented with complaints of amenorhoea for 8 weeks and lower abdominal pain for 4 hours with features of shock. Clinically the patient was diagnosed as a case of ruptured ectopic pregnancy. Cornual resection with left sided salpingectomy was done. Histopathology report confirmed interstitial tubal ectopic pregnancy which is a very rare and life threatening form of ectopic pregnancy. DOI: 10.3329/bmj.v39i1.6233 Bangladesh Medical Journal 2010; 39(1): 44-46